Comprehensive periodic health evaluations of 454 Norwegian Paralympic and Olympic athletes over 8 years: what did we learn? - Steffen, K.; Bahr, R.; Clarsen, B.; Fossan, B.; Fredriksen, H.; Gjelsvik, H.; Haugvad, L.; Hoksrud, A. F.; Iversen, E.; Koivisto-Mørk, A.; Moen, E.; Røstad, V.; et al. (British Journal of Sports Medicine, 2024)
Objective A periodic health evaluation (PHE) is a comprehensive and multidisciplinary investigation of athlete health widely used in elite sport, but its contents and benefits can be questioned. This study aimed to determine the prevalence of conditions identified by a PHE among Paralympic and Olympic athletes over four consecutive Games cycles from Rio de Janeiro 2016 to Beijing 2022 and to assess the benefits and potential pitfalls of a comprehensive PHE programme in detecting existing injuries, illnesses and other health issues.